Does Emotion Regulation Mediate the Relation Between Family-of-Origin Violence and Intimate Partner Violence? - Oliveros, Arazais D. (Journal of interpersonal violence, 2021)
Family-of-origin violence (FOV), including child maltreatment and exposure to interparental violence during childhood, is frequently cited as a risk factor for intimate partner violence (IPV) in adulthood. Emotion regulation (ER) difficulties have been linked to FOV and to IPV, but research has not identified the role of ER as a mechanism by which past exposure to FOV predicts current IPV. The current study examines whether greater FOV predicts ER difficulties, whether these difficulties can explain/mediate the relationship between FOV and IPV, and whether the process differs according to the gender of parent–child dyads. Emerging adult participants (475 women, 145 men) aged 18 to 30 years, who were in a current romantic relationship lasting at least 3 months, completed measures of past FOV, current difficulties in ER, and IPV perpetrated and experienced in current intimate relationships. ER difficulties mediated the relationship between FOV and current IPV; however, differences among specific types of FOV and gender were noted. Results support an intergenerational transmission of family violence and suggest that parent–child gender dyads influence this process.